Novel quantum well intermixing technique using gray mask technology for photonic integrated circuits - Ng, Seng Lee. (2008)
In this thesis, a low energy shallow ion implantation induced disordering process has been developed in order to tune the energy bandgap shift in InGaAs/InGaAsP multiple quantum well laser structures.